Mental Workload Analysis of Employees in the Customer Care Department of PT. XYZ Using NASA-TLX Method - Priska, Hersa Ajeng; Aurellia, Kamila; Putri, Febiola Andarista; Zaidan, Ahmad; Basumerda, Chancard (Proceeding International Conference on Religion, Science and Education, 2022)
PT. XYZ is an information communication technology (ICT) and telecommunications network company in Indonesia. The service process at the customer care section of PT. XYZ has the task of serving customers related to complaints, product installation, migration, and holding service duties at XYZ Plaza. Workers in the customer care department often complain of experiencing work stress. So it is necessary to repair and analyze the causes of mental workload using 6 factors, namely Mental Demand (MD), Effort (EF), Physical demand (PD), Temporal demand (TD), Performance (P), and Frustration level (FR). found in the NASA-TLX method. The results showed that the average weighted workload score was 71.62 from 8 workers, the score was included in the category of high level mental workload. So that some changes are needed to reduce the mental workload, in the form of considering rolling or distributing tasks evenly to each employee, especially for employees who experience overload and increase the number of workers, and provide periodic training.